Sistem Informasi Evaluasi Strategi Kualitas Layanan Berbasis Android di Griya Bandung Trade Center - Dheni Apriantsani Budiman; Agus Sugandi (Masoem University, 2020)
Griya Bandung Trade Center is a branch of YOGYA Group is a retail company with a format Supermaket and Departement Store which has served the people's needs for daily necessities. So Griya Bandung Trade Center must be able to provide satisfaction and make consumers become loyal to increase profits so that the company always maintains good relations with customers, But the system that runs is still not good. Griya Bandung Trade Center cannot manage feedback data yet obtained because there is no media or place for consumers to express disappointment, complaints about the services provided, or other feedback. Using the android mobile application because the use of cellphones is increasing every time. Delivering feedback through mobile media is considered effective because it is mobile and easy to use. The system development method used is OOAD (Object Oriented Analisis Design) which is a software engineering approach of a system consisting of a group of interacting real-world objects.